Advances in the Historical Archeology of Osorno, central-southern Chile - Urbina, Simón; Adán, Leonor; Cortés, Constanza; Sierralta, Simón (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2022)
The occupational history of the province and city of Osorno is documented in the context of pre-Hispanic and colonial intercultural relations of the so-called "upper border", in the southern portion of the Government of Chile. This work presents new results guided by the following objectives: 1) archaeologically characterize the current urban area of Osorno from systematic surveys and 2) describe the archaeological contexts identified in spatial, material and chronological terms. The research discusses the indigenous political-territorial organization in relation to the discontinuous process of urban implantation in the 16th and 18th centuries, emphasizing a reflection on the continuity and change in cultural patterns in the study area.